The fundamental anthropology of Rene Girard and the «concept of sacrifice» in M.Auezov's novel «The way of Abai» (Journal of Philosophy Culture and Political Science, 2024)
The article is devoted to the analysis of the ideas of the French-American philosopher, anthropologist, researcher in the field of problems of social philosophy, the creator of a fundamentally new theoretical approach, the so-called "fundamental anthropology", explaining the genesis and functions of traditional cultural institutions, Rene Girard. The universality of his theory lies in the fact that it can be applied by researchers in a wide variety of fields of science. Rene Girard offers a new look at the phenomenon of sacrifice, which played a significant role in archaic traditional cultures and accompanied all significant events of social and individual life. Unlike other anthropologists who considered sacrifice in archaic societies as a ritual designed primarily to appease deities, Girard considers this rite as underlying the genesis and structure of all myths and even the entire culture. Girard's thoughts on the relationship between culture and violence, the consideration of sacrifice as a fundamental ritual in the history of mankind can be reactalized in relation to Kazakh literary literature, in particular to the work of M. Auezov "The Way of Abai". In the novel by the Kazakh prose writer, dedicated to the description of the patriarchal-feudal Kazakh society, mytho-ritual structures and schemes, sacrificial practices and formulas play an important role, which can be traced throughout the novel chronotope. The mythologeme of sacrifice is embodied, in particular, in the scene of the collective execution of Kodar and Kamka. The philosophical and anthropological concept of Rene Girard makes it possible to identify the social significance of the ritual of sacrifice and the moral and ethical attitude towards the victim on the part of this societyKeywords: social philosophy, fundamental anthropology of Rene Girard, mythologeme of sacrifice, "The Way of Abai" by M. Auezov